Pengaruh Kualitas Pelayanan, Citra Perusahaan dan Tingkat Suku Bunga Terhadap Loyalitas Nasabah Pada PT.Bank Panin,Tbk., Di Kota Batam - Marlyna, Marlyna; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
PT's service quality, corporate image and interest rates. Bank Panin is very important in the banking industry, so special attention is needed to survive long-term competition. Relevant organizations can use this special attention to survive competition, accept challenges and develop in crisis. The purpose of this research is to determine whether service quality, corporate image and interest rates have an impact on customer loyalty. The main data collection method of this study is to distribute a questionnaire in the form of Google, which contains 375 respondents of active savings customers, and the sampling method used is random sampling. In order to generate considerable value, this study uses SPSS 25 version of the statistical analysis method. The results show that service quality, company image and interest rates have a positive and significant impact on customer loyalty. Some service quality has a positive but insignificant impact on customer loyalty. Corporate image has a positive and important impact on customer loyalty, while interest rates have a negative and insignificant impact on customer loyalty.